The non-reconstructive treatment of complete ACL tear with biological enhancement in clinical and preclinical studies: A systematic review - Yue Li; Sai Cheun Fu; Yau Chuk Cheuk; Guanyang Song; Hua Feng; Shu-Hang Yung (Elsevier, 2018)
Introduction: There is still controversy regarding the bio-enhanced non-reconstructive ACL treatment. Materials and methods: A search for articles in databases was performed in February 2017. The objective and subjective evaluations of clinical studies and biomechanical and histological data of preclinical studies were extracted. Results: Eighteen articles were included for analysis. In clinical studies, although subjective scores were significantly improved, the rate of re-operation rate was high. In preclinical studies, bio-enhancing techniques demonstrated promotion of the healing of ACL. Conclusions: The efficacy of biological enhancement cannot be validated in clinical studies. Preclinical studies showed improved biomechanical and healing potential.